Peran Imunologis Air Susu Ibu dalam Perlindungan Imun Bayi: Tinjauan Literatur - Pauzan; Ni Nyoman Ariwidiani (Jurnal Penelitian Pendidikan IPA, 2025)
Breast milk is the primary source of nutrition for newborns, providing not only essential nutrients but also rich bioactive components with immunological functions. It plays a critical role in the development and modulation of the infant’s immune system, through both innate immune components such as lactoferrin, lysozyme, and immune cells (macrophages, lymphocytes), and adaptive components like secretory immunoglobulin A (sIgA). Stunting in Indonesia is associated with a number of factors, including poverty, low levels of education, poor parenting techniques, and repeated infections that hinder the absorption of nutrients. This review aims to examine the role of breast milk in supporting the infant immune system, particularly in preventing infections, promoting the colonization of healthy gut microbiota, and stimulating mucosal immune development. The method used was a literature review of scientific articles published over the last 10 years (2015–2025) sourced from PubMed, ScienceDirect, and Google Scholar. The findings reveal that exclusively breastfed infants have a lower risk of respiratory and gastrointestinal infections, as well as atopic dermatitis, and demonstrate a more mature immune response compared to non-breastfed infants. The conclusion of this study confirms that breastfeeding significantly contributes to strengthening the infant immune system through immunoprotective and immunomodulatory mechanisms.